Sequenced Capability Model in Culinary SME Development Based on the Five Pillars of the Creative Economy - Rini Aristin; Nur Fathin Luaylik; Moh. Hamzah (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
Culinary SMEs face a growth paradox in which increasing market demand is not always supported by operational readiness, quality standardisation, and governance capability. In highly digitalised and easily imitable markets, maintaining product quality and service reliability has become essential for sustainable business growth. Previous studies have generally treated the five pillars of the creative economy industry, technology, resources, institutions, and financial intermediation as additive supporting factors, with limited attention to the interrelationships among these pillars and the sequencing of capability development. This study aims to develop a culinary SME development model based on the five pillars of the creative economy through a case study of a local tahu kocek enterprise. A qualitative exploratory–explanatory case study design was employed. Data were collected through semi-structured interviews, non-participant observation, and documentation and analysed using thematic analysis. The findings reveal that technology functions as an accelerator of market demand and business visibility, while successful scaling depends on operational readiness, human resources, and governance capability. The study also identifies a bottleneck in the form of misalignment between rapid demand growth and production capacity readiness. Based on these findings, the research develops a sequenced capability model consisting of operational foundations, controlled market acceleration, governance strengthening, and sustainable scaling through financing and capacity investment. Theoretically, the study extends the Resource-Based View and Dynamic Capabilities perspectives. Practically, the model may guide SME development strategies and capability-based policy interventions.